دور البلاعم في تطور الآفات التنشؤية داخل ظهارة عنق الرحم، دراسة شكليائية لخزع عنق الرحم في مشفى الأسد الجامعي - أحمد عيسى يوسف (Latakia University Journal -Medical Sciences Series, 2019)
تعتبر سرطانة عنق الرحم الواسعة الانتشار في العالم المتقدم سبباً مهماً للموت عند النساء، تحاول عناصر الالتهاب القضاء على العوامل المؤذية وتلعب دوراً سلبياً فيما يخص التنشؤ الورمي داخل ظهارة عنق الرحم، نشأ خلاف بين الباحثين حول دور الالتهاب في التنشؤ الورمي الظهاري لعنق الرحم. قمنا باستعمال المقاطع النسيجية المحضرة روتينياً والملونة H&E والتلوينات المناعية النسيجية الكيماوية (IHC) من أجل كشف مستضدات البلاعم CD68 عن طريق استخدام أضداد مضادة للمستضد السابق. حاولنا رصد تعداد البلاعم في مختلف آفات عنق الرحم التنشؤية الورمية والالتهاب. توصلنا إلى نتيجة هي أنه يزداد عدد البلاعم مع زيادة درجة الآفة التنشؤية داخل ظهارة العنق وفي السدى. تفترض هذه المعطيات إمكانية استعمال البلاعم في علاج الآفات التنشؤية الورمية العنقية وسرطانة العنق و تستعمل كواسم لتطور الآفات التنشؤية الورمية. The carcinoma of the cervix is widespread in the developed world. It is an important cause of death in women. Inflammatory reactions try to eliminate injurious factors, but they play a negative role with regard to neoplasia within the epithelium of the cervix. A dispute arises between researchers on the role of inflammation in cervical intraepithelial neoplasia. We have used tissue sections of routinely processed and H & E stain and immunohistochemistry (IHC) for the detection of macrophage CD68 + antigen by using anti-antibodies to the antigen previously. We have tried to count the macrophages in various degrees of cervical neoplastic lesions and inflammation. Our result is that increasing the number of macrophages with increasing the degree of the cervical squamous intraepithelial lesions in epithelium and in the stroma. These figures assume the possibility of the use of macrophages in the treatment of cervical squamous intraepithelial lesions and carcinoma and are used as markers for the development of cervical intraepithelial lesions.